The modern romantic in the world of ghosts. Gothic traditions in Jan Bittner’s novel Deník kastelána - Gawarecka, Anna (Poznańskie Studia Slawistyczne, 2011)
Romanticism, one of the most important philosophical and artistic periods in modern European culture, was never the mainstream tradition in Czech literature. Nor did the Gothic novel influence this literature in a significant way. In his Deník kastelána (Custodian’s Diary), Jan Bittner tries to use the formulas of traditional literary horror. The main aim of this renovation seems to be to search for a narrative form which is appropriate to show the problems and priorities of the modern self. The hero of the novel, who runs away from Prague and decides to live far from the postmodern civilization with its relativity of values and lack of metaphysical horizons, finds in the haunted baroque village castle a place where he can once again define the sense of life.